INFLUENCE OF FUNDS FOR RESULTS OF APBD: STUDY IN THE OIL AND GAS INDUSTRY IN INDONESIA - Subawan, Wawan; Padmodiningrat, Sumaryoto (Universitas Persada Indonesia YAI, 2019)
Sharing fund is the proportion possesed by local governments as oil and migasproducers. Along with fiscal decentralization and greater local autonomy presently, thesharing fund ought to be used for the wealth of these locals through APBD (Local Planningand Expendfture Budget). This study was aimed at identifying the effect of oil and gasupstream industry sharing fund on APBD. It was an explanative-associative study. Data werecollected through interviews, questionairre, observation and Ifterature. Data were analyzeddescriptively, and then treated by several assumption tests, approximated through pathcoefficient and confinnatory factor analysis. Subsequently, the author interpreted andmodified the model. The results indicated that the effects of sharing fund on APBD wassignificant. It means that the greater sharing fund will cause larger amount of APBD.